2018
DOI: 10.1155/2018/4670569
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aloe vera, Ananas comosus, and Sansevieria masoniana Cream on the Skin Wound Infected with MRSA

Abstract: The tropical area has a lot of herbal medicines such as Aloe vera (AV), Ananas comosus (AC), and Sansevieria masoniana (SM). All the three have a unique potential effect as an antibacterial and wound-healing promoter. The aim of this study is to explore the role of AV, AC, and SM on the skin wound infected with methicillin-resistant Staphylococcus aureus (MRSA). Forty-five adult female Sprague Dawley rats weighing 250–300 grams were divided into 5 groups. All the groups were exposed to two round full-thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The microbial growth inhibition capacity relies on the rich variety of phytochemicals including carbohydrates, saponin, flavonoids, phenols, alkaloid, anthocyanin and cyanine, glycosides, proteins, and phytosterols . Prakoso et al (2018) have explored the role of Aloe vera (L.) Burm.f. (AV), Ananas comosus (L.) Merr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial growth inhibition capacity relies on the rich variety of phytochemicals including carbohydrates, saponin, flavonoids, phenols, alkaloid, anthocyanin and cyanine, glycosides, proteins, and phytosterols . Prakoso et al (2018) have explored the role of Aloe vera (L.) Burm.f. (AV), Ananas comosus (L.) Merr.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that AV, AC, and SM have a similar potential effect on healing in the wound that was infected with MRSA compared to the groups C and BC (P <0.05). The study of Prakoso et al (2018) proved that AV, AC, and SM are widely used as traditional medicine and have a potential role in activating cluster of differentiation 8 [CD8 + , a transmembrane glycoprotein that serves as a co-receptor for the T cell receptor (TCR)] to infiltrate the wound tissue as the mechanism to eliminate MRSA infection (Wu and Xu, 2014). As T-cells are cytotoxic, CD8 + plays an important role not only in controlling the infection but also in eliminating the infected cells (Prakoso et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the phytochemical screening were similar to those of Prakoso et al [24] who demonstrated that A. comosus cream promoted healing in wounds infected with methicillin resistant Staphylococcus aureus. The global annual production of pineapple is estimated to be over 14 million tons [25] and the rind constitutes 10% of the weight of the fruit [26]. This implies that pineapple contributes significantly to agricultural waste worldwide and may thus have a negative impact on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Buah nanas dapat ditemukan pada hampir seluruh belahan dunia dan mempunyai banyak kandungan bermanfaat. Nanas mengandung enzim bromelain yang berguna untuk anti-inflamasi (damanik, 2019) (Prakoso, Setiyo Rini and Wirjaatmadja, 2018). Enzim ini dapat mempercepat pemulihan saat terjadi luka atau peradangan (Rahayu, Agustina and Tjandrawinata, 2017).…”
Section: Pendahuluan unclassified